Hubungan Sanitasi Lingkungan Dengan Personal Hygiene Terhadap Kejadian Balita Stunting Di Wilayah Kerja Puskesmas Kalirejo Kecamatan Kalirejo Kabupaten Lampung Tengah - Friska, Yessy; Murwanto, Bambang; Barus, Linda; Rosita, Yeni (MIDWIFERY JOURNAL, 2025)
Background : Stunting in toddlers is a significant global health problem. In 2022, there were 148.1 Million children affected, which is 22.3% of children worldwide. Most of these children Live in Asia (52%) and Africa (43%) (WHO, 2023). UPTD Kalirejo Health Center is one of the stunting locus health centers. Based on the Electronic Reporting and Reporting of Community-Based Nutrition (ePPGBM) report of Kalirejo Health Center which was seen in August 2024, the number of stunted toddlers was 34 toddlers. Purpose : This study aims to determine the relationship between environmental Sanitation and personal hygiene on the incidence of stunting in toddlers. Methods : This study is a Quantitative study with a case control design. Data obtained from interviews and Observations of mothers of toddlers at the UPTD Kalirejo Health Center, Kalirejo District, Central Lampung Regency. The variables observed were environmental sanitation,Personal hygiene and the incidence of stunting. Result : From the research that has been done, there is a relationship between ownership of healthy Toilets and the incidence of stunting (p value = 0.000). There is a relationship between Ownership of clean water facilities and the incidence of stunting (p value = 0.000). There is A relationship between wastewater treatment and the incidence of stunting (p Value = 0.000). There is a relationship between waste processing and the Incidence of stunting (p value = 0.000). There is a relationship between CTPS personal Hygiene and the incidence of stunting (p value = 0.000). There is no relationship between personal hygiene Nail hygiene and the incidence of stunting (p value = 0.614)Result : The community must maintain environmental sanitation and implement good personal Hygiene as a sensitive intervention to contribute to reducing stunting. Keywords: environmental sanitation, stunting, personal hygiene ABSTRAK Latar Belakang : Stunting pada balita adalah masalah kesehatan global yang signifikan. Pada tahun 2022, ada 148,1 juta anak yang terkena, yang merupakan 22,3% dari anak- anak di seluruh dunia. Sebagian besar anak-anak ini tinggal di Asia (52%) dan Afrika (43%) (WHO, 2023). UPTD Puskesmas Kalirejo merupakan salah satu Puskesmas lokus stunting. Berdasarkan laporan Elektronik Pencatatan dan Pelaporan Gizi Berbasis Masyarakat (ePPGBM) Puskesmas Kalirejo yang dilihat pada bulan Agustus 2024 jumlah balita Stunting Sebanyak 34 Balita.Tujuan : Penelitian ini bertujuan untuk mengetahui hubungan antara sanitasi lingkungan dengan personal hygiene terhadap kejadian balita stunting.Metode : Penelitian ini merupakan penelitian kuantitatif dengan rancangan case control. data yang diperoleh dari hasil wawancara dan observasi terhadap ibu balita di UPTD Puskesmas Kalirejo Kecamatan Kalirejo Kabupaten Lampung Tengah. Variabel yang diamati yaitu sanitasi lingkungan, personal hygiene dan kejadian stunting.Hasil : Dari penelitiaan yang telah dilakukan bahwa ada hubungan antara kepemilikan jamban sehat dengan kejadian stunting (p value = 0,000). Ada hubungan antara kepemilikan sarana air bersih dengan kejadian stunting (p value = 0,000). Ada hubungan pengolahan limbah cair rumah tangga dengan kejadian stunting (p value = 0,000). Ada hubungan pengolahan sampah rumah tangga dengan kejadian stunting (p value = 0,000). Ada hubungan personal hygiene CTPS dengan kejadian stunting (p value = 0,000). Tidak ada hubungan personal hygiene kebersihan kuku dengan kejadian stunting (p value = 0,614)Kesimpulan : masyarakat harus menjaga sanitasi lingkungan dan menerapkan personal hygiene yang baik sebagai intervensi sensitive terhadap kontribusi penurunan stunting. Kata Kunci : Sanitasi Lingkungan , Stunting, Personal Hygiene